Analisis Pengaruh Metode Penggerusan Kaplet Paracetamol terhadap Kadar Bahan Aktif Obat - Amanda Aulia; Yuyun Febriani; Tri Puspita Yuliana (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
One of the drugs commonly used by the general public is paracetamol. This drug has relatively mild side effects compared to other drugs, so it is common to be prescribed for compounding pulmonary drugs for patients with certain doses There are two grinding methods used, namely a mortir and a blender. The purpose of this study was determined the variation effects in the dissolution speed and particle size on decreasing levels of paracetamol potency in each grinding methods. UV-Vis Spectrofotometer was used as quantitative methode. Based on the results, the percentage level of solubility velocity were in mortar: 70.54% aquadest, 115.49% ethanol, 96.10% acetone, 113.20% NaOH. In the blender: 65.44% aquadest, 88.14% ethanol, 48.31% acetone, 98.20% NaOH. Meanwhile, for variations in particle size, the mortar obtained: mesh20 101.82%, mesh40 117.73%, mesh80 80.91%, mesh100 113.20%. In the blender obtained: mesh20 96.98%, mesh40 88.40%, mesh80 69.06%, mesh100 99.11%. Furthermore, the statistical analysis by two-way anova obtained a significance value of 0.059 for variations in dissolution speed and 0.659 in particle size. In conclusion, there was an effect of variations in solvents but did not show an effect of variations in particle size on decreasing levels of active drug ingredients.